Modeling the Socialization of Artificial Intelligence Technologies in Accounting Using Structural Equation Modeling - Soleymanpoor, Sedigheh; Rezaei, Farzin; Biglar, Kumars; Kazemi, Hossein (Business, Marketing, and Finance Open, 2024)
The aim of this study is to model the socialization of artificial intelligence technologies in accounting using structural equation modeling. The research approach follows a grounded theory methodology combined with structural equation modeling. In this context, interviews were conducted with 12 participants, including engineers educated in artificial intelligence, board members, financial managers, accountants, and auditors, until theoretical saturation was reached. The results from the secondary coding process were categorized into 11 main themes, 35 sub-themes, and 6 categories: causal factors, core factors, strategies, mediators, actions, and outcomes. The target population for the quantitative part of this study consisted of all accountants. The questionnaire was distributed among the members of the target population via direct (in-person), electronic, virtual spaces, emails, and mail. Ultimately, 342 individuals responded to the questionnaire. To test the research hypotheses, correlation techniques using structural equation modeling were applied. The results of the analysis of findings from 28 hypotheses showed that training and awareness significantly and positively affect effective communication, the ability to collaborate with artificial intelligence, and the prevention of threats. Moreover, the interaction between artificial intelligence and humans significantly and positively impacts effective communication, the ability to collaborate with artificial intelligence, software compatibility, and threat prevention. Continuous evaluation and improvement also significantly and positively affect effective communication, the ability to collaborate with artificial intelligence, and the prevention of threats. Additionally, support from financial tools positively and significantly influences effective communication, collaboration with artificial intelligence, and the prevention of threats. Effective communication has a significant and positive effect on comprehensive and accurate financial reporting, intelligent financial management, and diversity and inclusion. The ability to collaborate with artificial intelligence has a significant and positive effect on comprehensive and accurate financial reporting, intelligent financial management, and diversity and inclusion. Software compatibility positively and significantly impacts intelligent financial management and diversity and inclusion. Finally, the prevention of threats significantly and positively influences comprehensive and accurate financial reporting, intelligent financial management, and diversity and inclusion. The results indicate that there are fundamental infrastructures and technologies that can assist in the socialization of artificial intelligence in the field of accounting. Furthermore, accountants can play a crucial role in the effective use of artificial intelligence by providing relevant financial information to financial stakeholders and supporting financial information.